Original Method to Predict and Monitor Carbon Deposition on Ni-Based Catalysts During Dry Reforming of Methane - Ahmed, Rawaz; Sasaki, Takehiko; Olea, Maria (Frontiers in Chemical Engineering, 2020)
Although the catalytic reforming of methane with carbon dioxide, also known as dry reforming, has recently attracted considerable attention due, the one hand, to the simultaneously utilization of two greenhouses with high environmental impact and, the other hand, to produce syngas with a lower H2/CO ratio than those available from steam reforming and partial oxidation of methane, which is preferred for the synthesis of valuable oxygenated chemicals and long-chain hydrocarbons, has not yet been commercialized. Low-cost Ni-based catalysts with high activity were developed. However, due to their major drawbacks, which are carbon formation and Ni particles sintering at the high temperatures requires by the endothermic reaction, their industrial applicability is limited. What is more, access to advanced characterization techniques is needed to monitor coke deposition and to assess the efficiency of the dry reforming process, access which can be challenging for small and on-site laboratories. The focus of this current study is on the development and testing of a simple carbon deposition prediction method, easily accessible, based on the comparison of the gas composition measured at the exit of the reactor with the theoretical one, calculated based on the process thermodynamics. Trustworthy results, confirmed by SEM and TGA/DSC measurements, were obtained when the method was applied for the monometallic, Ni/SBA-15, prepared by wet impregnation, and bimetallic, Ni-Co/SBA-15 and Ni-La/SBA-15 samples, prepared by impregnation but co-impregnation as well, with different metal loading. The dry reforming process was performed at four temperatures, 550, 600, 650 and 700°C, respectively.